Use of simvastatin in the prevention of cyclophosphamide-induced ureteral mucositis - Maia, Beatriz Stephanie da Silva; Celani, Lívia Medeiros Soares; Moreira, Marília Daniela Ferreira de Carvalho; Araújo-Filho, Irami; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2018)
Purpose: This study was designed to investigate the pharmacological efficacy of simvastatin against ureteral mucositis cyclophosphamide-induced. Methods: Wistar rats weighing 287±14g were used. A single dose of cyclophosphamide (CYP) 200mg/kg IP + oral simvastatin (10mg/kg) were administered in the (CYP/SIMV) group (n=6), In the group (CYP/SAL) (n=6), saline v.o. was administered. The animals were weighed daily. After 7 days of CYP administration, blood was collected by cardiac puncture under anesthesia. After euthanasia, uterers were collected for histopathology. Serum TNF-?, IL-1?, IL-6 were determined by ELISA. Results: CYP-induced ureteral mucositis in rats resulted in a significant increased level of serum cytokines (TNF-?, IL-1b, IL-6). Simvastatin treated rats showed significant decreased level of inflammatory cytokines. In body weight records, CYP-treated rats showed visible significant body mass loss compared to untreated rats (p<0.05). Edema and inflammatory cells in ureter tissues were reduced after simvastatin treatment, as demonstrated in histological H-E staining. Conclusion: In conclusion, our current findings provided scientific evidence that oral simvastatin positively influenced benefits against cyclophosphamide-induced ureter mucositis, which possibly has occurred by inactivating cytokines.